2009
DOI: 10.1093/qjmed/hcp162
|View full text |Cite
|
Sign up to set email alerts
|

Are clinical parameters and biomarkers predictive of severity of acute pulmonary emboli on CTPA?

Abstract: These findings suggest that clinical parameters and biomarkers have a role in predicting the radiological severity of PE. These data support the need for further studies of risk stratification in patients presenting with acute PE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
31
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 23 publications
8
31
2
Order By: Relevance
“…According to Ghaye et al (10) and van der Meer et al (9), RV/LV ratio is a strong predictor of the severity of PE and patient outcome. This is in contrast to the studies of Araoz et al (11) and Jeebun et al (15), in which no association between the RV/LV ratio and death was reported. Similarly, in our study, RV/LV ratio did not predict mortality at 30-day followup.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…According to Ghaye et al (10) and van der Meer et al (9), RV/LV ratio is a strong predictor of the severity of PE and patient outcome. This is in contrast to the studies of Araoz et al (11) and Jeebun et al (15), in which no association between the RV/LV ratio and death was reported. Similarly, in our study, RV/LV ratio did not predict mortality at 30-day followup.…”
Section: Discussioncontrasting
confidence: 95%
“…The strong correlation between troponin I levels and both PAOI and RV/LV ratio has recently been emphasized by Shokoohi et al (14) and Jeebun et al (15). Consistent with these studies, we also found a significant but low correlation between troponin I levels and both PAOI and RV/LV ratio.…”
Section: Discussionsupporting
confidence: 92%
“…The level of d-dimers has been shown to correlate with right heart dysfunction and clot burden as well as to be a negative outcome predictor, since short and long term survival after acute PE is limited with increasing d-dimer levels [25][26][27][28][29][30]. However, keeping in mind the low specificity of this test, the mean d-dimer level was also slightly elevated in the control group without PE, but it was significantly lower than in patients with PE.…”
Section: Discussionmentioning
confidence: 99%
“…15 studies were initially excluded [10,19,20,22,26,31,33,35,38,39,41,43,46,50,52]. For six of them, the inclusion in the analysis was possible following contact with the authors [22,35,38,39,43,52].…”
Section: Meta-analysis Of Ct Assessed Right Ventricle Dilationmentioning
confidence: 99%